Model Transformasi Pendidikan Pondok Pesantren di Pulau Bawean Gresik - Asyhar, Ali (JOIES (Journal of Islamic Education Studies), 2016)
The topic of this research is the transformation model ofPesantren in Bawean with particular reference to Pondok Pesantren Hasan Jufri, Manbaul Falah and Nurul Ikhlas. The results of the research are described as follows: first, the transformation of Pesantren Hasan Jufri and Manbaul Falah took place by the establishmentof formal educational institutions. While the Pesantren Nurul Ikhlas Islmic does not establishthe formal educational institutions.Second, the aspects that have undergone transformation in Pesantren HasanJufri and Mambaul Falah include vision, mission, objective, curriculum, learning method, educators, students,media and infrastructure. Whereas the Pesantren Nurul Ikhlas has transformed onlyin learning methods Third, the model of the transformation in Hasan Jufri and Manbaul Falah is holistic transformation. While, the model of tranformation in Pesantren Nurul Ikhlas is partial transformation. Fourth,factors that influence the transformation of these pesantrens are the kiai's leadership and modernization characterized by the rapid flow of information and encouragement of santri and alumni.The inhibiting factor is the conservative view of some people that formal certificates are not required. It is enough for them to hold the salaf courses, while formal schools areestablished conductedoutside the pesantrens.